The role of skills in winning in different types of set in women`s volleyball - Drikos, S.; Angelonidis, Y.; Sobonis, G. (International Journal of Performance Analysis in Sport, 2018)
The aim of this study is to identify volleyball performance indicators that best discriminate between winning and losing teams in a set according to the level of competitiveness. The data have been collected from teams` performances (N = 438) in all sets played between top four teams in the final ranking of women`s Greek volleyball league for five periods. Clusters analysis established three different groups of sets according to set final score difference: two to three points (balanced), four to seven points (semi-balanced) and more than seven points (unbalanced). A 3 × 2 MANOVA was then performed on twelve performance indicators reflecting expressions of five basic skills of the game (serve, pass, attack 1 and 2, block). The analysis revealed significant multivariate differences in the type of result and in its interaction with the type of set. A follow-up discriminant analysis showed that the effectiveness of attacks 1 and 2 are the most important performance indicators for all the set types. The discriminant function classified correctly more cases as the score difference got higher. Especially for balanced sets, 62% were correctly classified, allowing space for further improving the critical performance indicators. These results suggest that training of a women`s volleyball team should emphasise more on improving offensive abilities.